2013
DOI: 10.1007/s11356-013-2324-3
|View full text |Cite
|
Sign up to set email alerts
|

Energy-dependent uptake of benzo[a]pyrene and its cytoskeleton-dependent intracellular transport by the telluric fungus Fusarium solani

Abstract: In screening indigenous soil filamentous fungi for polycyclic aromatic hydrocarbons (PAHs) degradation, an isolate of the Fusarium solani was found to incorporate benzo[a]pyrene (BaP) into fungal hyphae before degradation and mineralization. The mechanisms involved in BaP uptake and intracellular transport remain unresolved. To address this, the incorporation of two PAHs, BaP, and phenanthrene (PHE) were studied in this fungus. The fungus incorporated more BaP into cells than PHE, despite the 400-fold higher a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 36 publications
4
28
0
Order By: Relevance
“…Although PAHs are subject to a range of dissipation processes including volatilization, photooxidation, chemical oxidation, sorption, leaching, and biological process ( Stringfellow and Alvarez-Cohen, 1999 ; Chen and Ding, 2012 ; Thion et al, 2012 ; Xu et al, 2013 ), biodegradation by microorganisms has been generally considered to be one of the primary means for the removal of PAHs from environment ( Bamforth and Singleton, 2005 ; Haritash and Kaushik, 2009 ; Wang et al, 2009 ; Chen et al, 2010 ; Zeng et al, 2010 ; Xu et al, 2013 ). It was observed that for most microorganisms, the PAHs biodegradation process occurred intracellularly ( Xu et al, 2013 ) and the trans-membrane transport of PAHs was the first step in biodegradation ( Fayeulle et al, 2014 ; Li et al, 2014 ). In addition, the biosorbed PAHs in microorganisms might be readily accessible for biodegradation by stimulating the intracellular physico-chemical and biochemical processes with prolonging the incubation time ( Chen et al, 2010 ; Ning et al, 2010 ; Chen and Ding, 2012 ; Thion et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although PAHs are subject to a range of dissipation processes including volatilization, photooxidation, chemical oxidation, sorption, leaching, and biological process ( Stringfellow and Alvarez-Cohen, 1999 ; Chen and Ding, 2012 ; Thion et al, 2012 ; Xu et al, 2013 ), biodegradation by microorganisms has been generally considered to be one of the primary means for the removal of PAHs from environment ( Bamforth and Singleton, 2005 ; Haritash and Kaushik, 2009 ; Wang et al, 2009 ; Chen et al, 2010 ; Zeng et al, 2010 ; Xu et al, 2013 ). It was observed that for most microorganisms, the PAHs biodegradation process occurred intracellularly ( Xu et al, 2013 ) and the trans-membrane transport of PAHs was the first step in biodegradation ( Fayeulle et al, 2014 ; Li et al, 2014 ). In addition, the biosorbed PAHs in microorganisms might be readily accessible for biodegradation by stimulating the intracellular physico-chemical and biochemical processes with prolonging the incubation time ( Chen et al, 2010 ; Ning et al, 2010 ; Chen and Ding, 2012 ; Thion et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…8. Compared with DOX-NPs without inhibitor, the average cellular fluorescence intensity of DOX was significantly reduced after treating with sodium azide (energy inhibitor) [38], colchicine (macropinocytosis inhibitor) [37], and indomethacin (caveolae-mediated endocytosis inhibitor) [39], showing that the cellular uptake of DOX-NPs might be energy dependent endocytosis processes by caveolae-mediated and macropinocytosis pathways. However, no significant inhibition of cellular uptake of DOX-NPs was observed after treating with chlorpromazine (clathrin mediated endocytosis inhibitor), suggesting the internalization of DOX-loaded nanoparticles was independent of clathrin.…”
Section: Cellular Toxicity and Cellular Uptakementioning
confidence: 99%
“…The details for the mechanisms of microbial degradation are reported elsewhere (Fritsche and Hofrichter, 2008). Despite numerous recent studies have been undertaken on the bioremediation of PAHs and VOCs employing bacteria (Hamed et al, 2012;Lee et al, 2015;Li et al, 2015;Murínová et al, 2014;Yao et al, 2015) and fungi (Fayeulle et al, 2014;Isola et al, 2013;Mouhamadou et al, 2013;Reyes-César et al, 2014), the knowledge about complete removal of bound toxic compounds by microbial activity is still unclear. Pseudomonas spp., Sphingomonas spp., Flavobacterium spp., Burkholderia spp.…”
Section: Bioremediation Of Pahs and Vocs: Role Of Microbial Degradationmentioning
confidence: 99%